الانغماس المسرحي، بيئة جديدة للتعليم الإبداعي - بلغدوش, فتيحة (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2023)
يعد المسرح التعليمي أحد الروافد الأساسيّة لاستزراع متعلمين مبدعين، إذ يجعل العمليّة التعليمية التعلميّة أكثر حيويّة وجاذبيّة، الأمر الذي يزيد من الحافز التعلمي لدى متعلم اللغة العربيّة، والتخفيف من جفاف المناهج الدّراسيّة وكثافتها، أضف إلى ذلك فإنّ المسرح التعليمي يشجّع المتعلمين على استخدام المستويات العليا للتفكير من خلال العمل التعاوني مع الأقران، حيث يساعد على بناء الأفكار لفهم أعمق للظواهر الاجتماعيّة والعلميّة واللغويّة، خاصة في المراحل الأولى من تعلمهم وبالتالي فإن توفير المسرح ضمن المناهج الدّراسيّة كفيل بتوجيه قدرات المتعلمين وإثارتهم من أجل الإفصاح عن قدراتهم الإبداعيّة وإثراء مخزونه اللغوي فضلا عن ذلك فإن المسرح المدرسي يساهم في بناء ثقة المتعلمين حيث يمكّنهم من التغلّب على الخوف، وكذا حل مشكلاتهم، ومواجهة مواقفهم الحياتيّة بشجاعة وثبات. Educational theatre is one of the basic tributaries to cultivate creative learners,as it makes the teaching-learning process more lively and attractive,which increases the learning motivation of the Arabic language learner, and reduces the dryness and density of the curriculum. Moreover, educational theatre encourages learners to use higher levels of thinking through collaborative work with peers, as it helps build ideas for a deeper understanding of social, scientific,and linguistic phenomena,especially in the early stages of their learning. Therefore, providing theatre within the school curricula is sufficient to direct the learners’ abilities and excite them in order to reveal their creative abilities and enrich their linguistic repertoire. In addition, school theatre contributes to building learners’ confidence,as it enables them to overcome fear. As well as solving their problems and facing their life situations with courage and steadfastness.